Evaluating the Impact of Preoperative Pain Intensity Ratings on Narcotics Use in Spine Surgery Candidates With Affective Disorders. (16th November 2020) - Christian, Zachary; Aoun, Salah G; Afuwape, Olusoji A; Barrie, Umaru; Adeyemo, Emmanuel; Badejo, Olatunde; Dosselman, Luke; Pernik, Mark N; Hall, Kristen; Reyes, Valery Peinado; Bagley, Carlos A
Abstract: INTRODUCTION: Depressive disorder has been shown to be an independent risk factor for opioid abuse and increased perception of postoperative pain. However, the relationship between AD and preoperative quality of life, narcotic intake, and pain, has not been previously explored in spine surgery candidates. METHODS: The records of 117 consecutive adult patients who underwent elective spinal surgery between October 2016 and August 2017 at a single institution were reviewed. Inclusion criteria also included patients who underwent a preoperative pain assessment within 30 days prior to their planned surgery using the Patient-Reported Outcomes Measurement Information System 29 (PROMIS-29). Primary outcomes included preoperative ratings of anxiety, depression, pain, preoperative narcotic use, and postoperative hospital length of stay, intra- and post-operative complications in patients with AD (depression, anxiety, bipolar disorder, and/or PTSD) compared to controls. RESULTS: The average rating of Pain Intensity was notably higher in the AD group compared controls ( P  = .004). The AD group had more patients complaining of high pain levels (>6) compared to the controls ( P  = .026). Controls with high-pain had a greater incidence of preoperative narcotic use compared to the low-pain cohort ( P  = .029). However, there was no difference in the actual dose of daily narcotic medication taken in MEDD between the AD and control groups, or between the low- and high-pain score groups in the control and AD groups respectively. Surgical procedure types, hospital length of stays, and perioperative complications were comparable in the AD and control groups. Patients who underwent lumbar short surgeries reported high levels of preoperative pain intensity, while patients who underwent anterior cervical procedures on average reported lower levels in both groups. CONCLUSION: ADs may impact the degree of preoperative pain interference and the intake of narcotic medication independently from pain intensity ratings. These findings highlight the importance of detecting and treating depression and anxiety in patients suffering from spine disorders, regardless of surgical intervention planning.